PENGARUH PEMBINAAN DAN PENGAWASAN TERHADAP KINERJA APARATUR INSPEKTORAT KOTA PALU - Sari, Frisusmita (Katalogis, 2016)
The objectivities of this research are: 1) to determine the influence of guidance and supervision on apparatus performance in The Inspectorate Office of Palu, 2) to determine the influence of guidance on apparatus perfoemance in The Inspectorate Office of Palu, 3) to determine the influence of supervision on apparatus performance in The Inspectorate Office of Palu. This research means to verify the relationship between variables and it involbes 36 respondents who selected through census sampling technique. The results show that : 1) guidance and supervision have significant influence on apparatus perfermonce in The Inspectorate Office of Palu, 2) guidance has significant influence on apparatus performance in The Inspectorate Office of Palu, 3) supervision has significant influence on apparatus performance in The Inspectorate Office of Palu.